Supervisor Variance in Psychotherapy Outcome in Routine Practice: A Replication. (January 2020) - Whipple, Jason; Hoyt, Tyler; Rousmaniere, Tony; Swift, Joshua; Pedersen, Tyler; Worthen, Vaughn
This study is a replication of Rousmaniere et al., in which no differences in client outcome between supervisors were found and few differences in client outcome due to either degree level or experience as a supervisor were found. Hierarchical linear modeling was used to determine variance estimates in client outcome accounted for by supervisors. The longitudinal archival data set consisted of 3, 030 clients, 80 therapists, and 39 supervisors at a University Counseling Center in the Rocky Mountains. Therapists practiced psychodynamic, strategic, cognitive behavioral therapy (CBT), solution-focused, and family systems approaches. Average improvement of clients was 7.91 points across supervisors using the Outcome Questionnaire-45.2 (OQ-45.2). Consistent with Rousmaniere et al., the amount of variance in client outcome attributable to clinical supervision was less than 1%. Implications indicate supervision may be enhanced by increased focus on aiding professional development of supervisees and emphasized future clarification surrounding the role of improvement of client welfare by supervisors.